HOMOSEKS DAN LESBIAN PERSPEKTIF HUKUM ISLAM - Fatmawati, Fatmawati (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
Gay and lesbian issued in this paper analyzed from two perspectives, namely the views of Islamic law against sexual perversion in the form of gay and lesbian, and the sanctions given for gay and lesbian. By using a normative approach, it was concluded that the scholars agreed that homosexual and lesbian acts are haram/ prohibited. However, scholars are still different opinions in determining punishment for the perpetrators. Some scholars argue that the perpetrators should be killed or stoned both muhsan and ghairu muhsan. Some scholars assign taâzir penalty on the grounds that this action is only one form of immorality. That is not specified shape and just love on the penalty spot unwanted by normal instincts. Because of that, perpetrators donât not gain had punishment.